2005
DOI: 10.1111/j.0001-6349.2005.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron prophylaxis during pregnancy – How much iron is needed? A randomized dose– response study of 20–80 mg ferrous iron daily in pregnant women

Abstract: In Danish women, a supplement of 40 mg ferrous iron/day from 18 weeks of gestation appears adequate to prevent iron deficiency in 90% of the women and iron deficiency anemia in at least 95% of the women during pregnancy and postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
85
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 36 publications
9
85
0
5
Order By: Relevance
“…In agreement with previous studies, 1,6 we found an almost 50% decline in the concentration of cobalamins during late pregnancy (Table 1). A small increase in MMA was observed during pregnancy and post partum (Table 1) but we question whether this is caused by an increased metabolic rate during pregnancy and lactation rather than a sign of vitamin B12 deficiency.…”
supporting
confidence: 93%
“…In agreement with previous studies, 1,6 we found an almost 50% decline in the concentration of cobalamins during late pregnancy (Table 1). A small increase in MMA was observed during pregnancy and post partum (Table 1) but we question whether this is caused by an increased metabolic rate during pregnancy and lactation rather than a sign of vitamin B12 deficiency.…”
supporting
confidence: 93%
“…4 A study of Danish pregnant women which evaluated the effect of 20, 40, 60, and 80 mg of iron daily found 20 mg was inadequate to prevent ID in a substantial number of women and that 40 mg of iron prevented IDA in more than 95% of the women. 19 Our findings reveal a high prevalence of women taking popular pregnancy MVs, with most containing only 5 mg of elemental iron per tablet. Furthermore, it appears many women may not take the recommended number of tablets on a daily basis.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, in a randomised controlled trial with iron supplements in varying doses, no difference in occurrence of side-effects was reported in the groups who received 20, 40, 60 or 80 mg iron per day 42 . However, this may be a reason for not taking iron supplements, as many of the available products contain 100 mg iron per daily dosage.…”
Section: Discussionmentioning
confidence: 91%